2023
DOI: 10.3389/fmolb.2023.1183530
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ferroptosis-related genes as potential diagnostic biomarkers for diabetic nephropathy based on bioinformatics

Binbin Guo,
Minhui Li,
Peipei Wu
et al.

Abstract: Objective: This study investigated to probe ferroptosis-related diagnostic biomarkers and underlying molecular mechanisms in Diabetic nephropathy (DN).Methods: GSE30122 and GSE1009 from GEO database were used as training and verification sets, respectively, to screen differentially expressed ferroptosis-related genes (FRGs). These genes were further analyzed using GO, KEGG, and GSEA methods, and screened with PPI, LASSO, and SVM-RFE to identify ferroptosis-related diagnostic biomarkers for DN. A diagnostic mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Importantly, our results showed that kidney tea mainly participated in ferroptosis, arginine biosynthesis and mTOR signaling pathway. Ferroptosis, an iron-dependent form of regulated cell death, is considered to be closely associated with DN pathogenesis ( Guo et al, 2023 ; Kim et al, 2023 ; Tsai et al, 2023 ). Attractively, emodin inhibited ferroptosis by promoting the expression of nuclear factor E2-related factor 2 (NRF2), thereby reducing reactive oxygen species (ROS) production and ameliorating renal injury in DN rats ( Ji et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our results showed that kidney tea mainly participated in ferroptosis, arginine biosynthesis and mTOR signaling pathway. Ferroptosis, an iron-dependent form of regulated cell death, is considered to be closely associated with DN pathogenesis ( Guo et al, 2023 ; Kim et al, 2023 ; Tsai et al, 2023 ). Attractively, emodin inhibited ferroptosis by promoting the expression of nuclear factor E2-related factor 2 (NRF2), thereby reducing reactive oxygen species (ROS) production and ameliorating renal injury in DN rats ( Ji et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous network pharmacology studies (71, 72) on traditional Chinese medicine or Chinese herbal medicine for treating DN did not involve in-depth analysis of human samples but used animal samples or simply collected disease targets from GEO datasets. Previous machine learning studies (73)(74)(75) on DN mainly analyzed it from the perspectives of immunity, oxidative stress, programmed cell death, etc., and were mainly used to screen and identify genetic biomarkers, while this study used the target as a link and started from the perspective of drug intervention in disease to explore the multi-faceted mechanisms of TMJT in treating DN, and verified the results by dataset analysis, molecular docking, MR analysis, and other methods. Therefore, compared with other studies, this study is more comprehensive and has more guiding significance for clinical medication.…”
Section: The Strengths and Limitations Of This Studymentioning
confidence: 99%